Music and the Meeting of Human Minds - Harvey, Alan R. (Frontiers in Psychology, 2018)
Over tens of thousands of years of human genetic and cultural evolution, many types and varieties of music and language have emerged; however, the fundamental components of each of these modes of communication seem to be common to all human cultures and social groups. In this brief review, rather than focusing on the development of different musical techniques and practices over time, the main issues addressed here concern: (i) when, and speculations as to why, modern Homo sapiens evolved musical behaviors, (ii) the evolutionary relationship between music and language, and (iii) why humans, perhaps unique among all living species, universally continue to possess two complementary but distinct communication streams. Did music exist before language, or vice versa, or was there a common precursor that in some way separated into two distinct yet still overlapping systems when cognitively modern Homo sapiens evolved? A number of theories put forward to explain the origin and persistent universality of music are considered, but emphasis is given, supported by recent neuroimaging, physiological and psychological findings, to the role that music can play in promoting trust, altruistic behavior, social bonding, and cooperation within groups of culturally compatible but not necessarily genetically related humans. It is argued that, early in our history, the unique socializing and harmonizing power of music acted as an essential counterweight to the new and evolving sense of self, to an emerging sense of individuality and mortality that was linked to the development of an advanced cognitive capacity and articulate language capability.